China's Pattern of Growth : Moving To Sustainability And Reducing Inequality - Kuijs, Louis (The World Bank, 2005)
The authors study the sources and pattern of China's impressive economic growth over the past 25 years and show that key issues currently of concern to policymakers-widening inequality, rural poverty, and resource intensity-are to a large extent rooted in China's growth strategy, and resolving them requires a rebalancing of policies. Using both macroeconomic level and sector data and analyses, the authors extend the growth accounting framework to decompose the sources of labor productivity growth. They find that growth of industrial production, led by a massive investment effort that boosted the capital/labor ratio, has been the single most important factor driving GDP and overall labor productivity growth since the early 1990s. The shift of labor from low-productivity agriculture has been limited, and, hence, contributed only marginally to overall labor productivity growth. The productivity gap between agriculture and the rest of the economy has continued to widen, leading to increased rural-urban income inequality. Looking ahead, the authors calibrate two alternative scenarios. They show that continuing with the current growth pattern would further increase already high investment and saving needs to unsustainable levels, lower urban employment growth, and widen the rural-urban income gap. Instead, reducing subsidies to industry and investment, encouraging the development of the services industry, and reducing barriers to labor mobility would result in a more balanced growth with an investment-to-GDP ratio that is consistent with the medium-term saving trend, faster growth in urban employment, and a substantial reduction in the income gap between rural and urban residents